2019
DOI: 10.1080/21691401.2019.1637884
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Involvement of NORAD/miR-608/STAT3 axis in carcinostasis effects of physcion 8-O-β-glucopyranoside on ovarian cancer cells

Abstract: We planned to dig the carcinostasis activity of physcion 8-O-b-glucopyranoside (PG) in ovarian cancer cells and explored whether long non-coding RNA NORAD was the potential cause of the carcinostasis impact of PG. The impacts of PG on the tumour cell behaviours (including cell viability, apoptosis, migration and invasion) of SKOV3 cells were grabbed. The levels of NORAD in cancer tissues and cell lines were determined; afterwards, the impacts of abnormal expression of NORAD on the tumour cell behaviours of SKO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…However, the role of NORAD in DR has not been reported. Previously, Yang et al proved that NORAD/miR-608/STAT3 axis in carcinostasis effects the physcion 8-O-bglucopyranoside on ovarian cancer cells [23], implying the near correlation between miR-608 and NORAD. Currently, few reports were focussed on miR-608 in DR. To the contrary, miR-125 was found in DR in the HG-disposed condition, and it can be associated with cell apoptosis under HG-disposed condition [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of NORAD in DR has not been reported. Previously, Yang et al proved that NORAD/miR-608/STAT3 axis in carcinostasis effects the physcion 8-O-bglucopyranoside on ovarian cancer cells [23], implying the near correlation between miR-608 and NORAD. Currently, few reports were focussed on miR-608 in DR. To the contrary, miR-125 was found in DR in the HG-disposed condition, and it can be associated with cell apoptosis under HG-disposed condition [24].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the roles of NORAD in diseases have been mainly focused on its effects on tumors. For example, NORAD could promote the development of ovarian cancer, gastric cancer, and pancreatic cancer colorectal cancer [21][22][23][24]. No studies have been reported on the effects of NORAD on endothelial cell injury and atherosclerosis.…”
Section: Agingmentioning
confidence: 99%
“…Several studies have revealed that NORAD had effects on tumor cell proliferation, apoptosis, and migration via binding with miRNAs or proteins 13 . NORAD was identified as an oncogene in pancreatic and ovarian cancer 14,15 , while its roles in lung and breast cancers have been controversial, indicating a context-dependent role in cancer progression 16 . The function and mechanism of NORAD involved in regulating EC formation and progression remain unexplored.…”
Section: Introductionmentioning
confidence: 99%